Examining the Interaction Between Behavioral and Emotional Engagement on Cognitive Engagement: A Mediation Analysis - Maharani, Amanda (CV. Akademi Merdeka, 2025)
This study aims to examine the effects of behavioral and emotional engagement on cognitive engagement among elementary school students using structural modeling. Data were collected from 240 students in grades 4-6 using a 15-item Likert-scale questionnaire. Confirmatory Factor Analysis (CFA) was used to test construct validity and reliability, followed by Structural Equation Modeling (SEM) to examine interdimensional relationships. The results showed that behavioral engagement had a positive effect on both emotional and cognitive engagement, while emotional engagement also positively influenced cognitive engagement. However, the effects were relatively small, and emotional engagement did not significantly mediate the relationship between behavioral and cognitive engagement. These findings emphasize the role of behavioral and emotional engagement in enhancing cognitive engagement, while suggesting that other contextual factors should also be considered. The proposed model demonstrated a good fit with the data and provides a basis for understanding student engagement in primary education.